The Concept of Infaq in The Qur’an According to Sayyid Quthb and Its Relevance to The Concept of Philanthropy - Akbar, A Fadly Rahman; Trisnani, Asif; Heriska, Rine (Fakultas Ushuluddin dan Dakwah Institut Al Fithrah Surabaya, 2025)
Social inequality is prevalent in society, where the rich are on top of their wealth and the poor are on the bottom with their poverty. The concept of philanthropy comes as an answer to this problem. However, the universal concept of philanthropy is used as a tool that can increase social inequality. In the Qur’an, there is the concept of infaq which can be used to overcome social inequality. Sayyid Quthb as a mufassir with his social style has his concept in understanding the concept of infaq in the Qur’an. As a whole concept, the concept of infaq in Sayyid Quthb's view has a coherent relevance to developing the concept of philanthropy. This study also aims to analyze the relevance of the concept of infaq in the Qur’an in Sayyid Quthb's view with the concept of philanthropy, so that the concept of infaq can strengthen the benefits of philanthropy more significantly. The approach used by researchers in this research is a thematic approach which includes library research. The method used in this research is a descriptive analysis. The result of this study is regarding Sayyid Quthb's interpretation of the concept of infaq in the Qur’an which is based on the theological dimension of infaq which is affiliated with a Muslim's devotion to Allah SWT and its form of jihād in fighting lust in humans. This theological dimension has a significant influence on the application of the social dimension of infaq in Sayyid Quthb's view. The theological dimension of the concept of infaq in the form of the principles of devotion and jihad to Allah SWT is the difference between the concept of infaq and the concept of philanthropy. The theological dimension in Sayyid Quthb's Infaq concept becomes a bulwark in the donation of wealth by a Muslim. The concept of philanthropy does not have this defense, so this concept is very easy to include elements that are not by human rights. The social dimension in the concept of infaq according to Sayyid Quthb is a sense of social solidarity that upholds compassion for fellow creations of Allah SWT. Thus, this social dimension can be a link between the concept of infaq in Sayyid Quthb's view and the concept of philanthropy.